Prognostic implications of N-terminal pro-B-type natriuretic peptide and high-sensitivity cardiac troponin T in EMPEROR-Preserved - Januzzi, James L.; Butler, Javed; Zannad, Faiez; Filippatos, Gerasimos; Ferreira, João Pedro; Pocock, Stuart J.; Sattar, Naveed; Verma, Subodh; Vedin, Ola; Iwata, Tomoko; Brückmann, Martina; Packer, Milton; et al. (JACC Heart failure, 2022)
Background - N-terminal pro-B-type natriuretic peptide (NT-proBNP) and high-sensitivity cardiac troponin T (hs-cTnT) are associated with disease severity and outcomes among patients with heart failure (HF) with preserved ejection fraction. - Objectives - The authors evaluated associations between both biomarkers and clinical outcomes in the EMPEROR-Preserved (Empagliflozin Outcome Trial in Patients with Chronic Heart Failure with Preserved Ejection Fraction) trial. - Methods - Of 5,988 study participants, 5,986 (99.9%) and 5,825 (97.3%) had available baseline NT-proBNP and hs-cTnT; postbaseline NT-proBNP was also available. Baseline characteristics were expressed by biomarker quartiles. The effect of empagliflozin on cardiovascular death/ HF hospitalization, the individual components, total HF hospitalizations, slope of decline of estimated glomerular filtration rate (eGFR), and a composite renal endpoint were examined across biomarker quartiles. Change in NT-proBNP across study visits as a function of treatment assignment was also assessed. - Results - Higher baseline NT-proBNP and hs-cTnT concentrations were associated with more comorbidities and worse HF severity. Incidence rates for cardiac and renal outcomes were 2- to 5-fold higher among those in the highest vs lowest NT-proBNP or hs-cTnT quartiles. Empagliflozin consistently reduced the risk for cardiovascular events and reduced slope of eGFR decline across NT-proBNP or hs-cTnT quartiles. Empagliflozin treatment modestly lowered NT-proBNP; by 100 weeks, the adjusted mean difference in NT-proBNP from placebo was 7%. Increase in NT-proBNP from baseline to 12 weeks was strongly associated with risk of cardiovascular death/HF hospitalization. - Conclusions - The benefit of empagliflozin on cardiac outcomes and decline of eGFR is preserved across the wide range of baseline NT-proBNP and hs-cTnT evaluated. Empagliflozin modestly reduces NT-proBNP in HF with preserved ejection fraction. (EMPagliflozin outcomE tRial in Patients With chrOnic heaRt Failure With Preserved Ejection Fraction [EMPEROR-Preserved]; NCT03057951)